The Effect Of Compost From Household Waste And Liquid Organic Fertilizer ‎On Growth And Yield Of Pak Choi (Brassica rapa var. Chinensis)‎ - Krismawati, Amik; Sugiono, Sugiono (El-Hayah : Jurnal Biologi, 2021)
Objectives of the research were to study and create a technique in producing compost made of organic wastes from the household and its effect on growth and increase productivity of Pak Choi. The research was conducted from January to February 2017 in Karangploso, Malang, East Java. The research applied RBD with 4 replications. The treatments comprised of 2 types, such as compost of household waste that consisted of 3 levels as follow K1 = Organic wastes of household waste 100% + Superdegra decomposer + goat dropping + bran + molasses by dose 0.5 kg/polybag; K2 = Organic waste from household waste 100% + Superdegra decomposer + goat dropping + bran + molasses by dose 1.0 kg/polybag; K3 = Organic waste from household waste 100% + Superdegra decomposer + goat dropping + bran + molasses by dose 1.5 kg/polybag. Treatment of different concentrations of liquid organic fertilizer consisted of three levels that include C1 = 20 ml/500 ml water, C2 = 40 ml/500 ml water, and C3 = 60 ml/500 ml water. Data analysis used Analysis of Variance (ANOVA) and followed by LSD at level 5%. Results of analysis in the laboratory indicated that organic fertilizer from organic waste of the household waste 100% + Superdegra + goat dropping + bran + molasses produced C-organic = 18.89 and C/N-ratio = 17.33. Combination of treatments, which include organic waste (K3C2), will be able to produce Pak Choi 126.38 gram/polybag